Workload, Work Intensity, And Employee Stress: A Qualitative Study at A Cosmetics Factory In Sidoarjo - Moh. Juhri; Ahmad Dzulfikri Budi Kusworo (CV Putra Publisher, 2026)
Competition in Indonesia’s cosmetics industry is becoming increasingly fierce, requiring every company to operate effectively and efficiently to remain competitive. On the other hand, limited human resources and suboptimal work systems often force employees to handle heavy workloads and high work intensity. This study aims to understand and describe how workload and work intensity affect the stress levels experienced by employees at a cosmetics factory in Sidoarjo. The research method used is qualitative with a phenomenological approach to deeply uncover individuals’ subjective experiences. Data were collected through face-to-face interviews. Research findings indicate that employees’ workloads tend to increase due to limited human resources, operational constraints (such as delays in raw material delivery and machine breakdowns), and the accumulation of dual responsibilities (double job roles). The high intensity of work is reflected in a hectic work pace and the demand to complete tasks within tight deadlines. These conditions trigger varying levels of work-related stress, leading to physical exhaustion, disrupted rest periods, and emotional strain. Although employees have made independent efforts to adapt such as setting work priorities and discussing issues with colleagues this pressure cannot be fully resolved without a commitment to improving work systems and organizational support from company management.